Sample instructional materials in communication arts in III (English) for agricultural secondary schools - Cabansag, Delfin Ronquillo 1940- (1977)
This study was conducted in response to the new thrusts in education, that is, the development of an integral learning program, and with the latest revision in secondary education program aimed at equipping the student with occupational skills essential for gainful employment and for enhancing his trainability. This paper is an attempt to present sample instructional materials in Communication Arts III (English) for agricultural secondary schools. The writer prepared the sample instructional materials to serve as teacher's guide in an agricultural school like the Cagayan Valley Institute of Technology.